2014
DOI: 10.1021/ie5034045
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Development and Application of Plant-Based Bioflocculants and Grafted Bioflocculants

Abstract: Flocculation is extensively employed for clarification through sedimentation. Application of ecofriendly plant-based bio-flocculants in wastewater treatment has attracted significant attention lately with high removal capability in terms of solids, turbidity, colour and dye. However, moderate flocculating property and short shelf life restrict their development. In order to enhance the flocculating ability, natural polysaccharides derived from plants are chemically modified by inclusion of synthetic, non-biode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 96 publications
0
39
0
Order By: Relevance
“…There is clearly an economic drawback in using either form of bio-flocculant due to the increased dosage required. Yet, the major importance of their applications in food and other industries, and the value of its substantial benefit to environment and human health may offset this extra cost in circumstances where the use of polymeric flocculants is undesirable or prohibited (Lee et al 2014). In addition, the sludge or flocs formed are biodegradable and safely to be landfilled without further treatment and would reduce the overall treatment cost.…”
Section: Comparison Of Sludge Dewatering Abilities Of Bio-flocculantsmentioning
confidence: 99%
“…There is clearly an economic drawback in using either form of bio-flocculant due to the increased dosage required. Yet, the major importance of their applications in food and other industries, and the value of its substantial benefit to environment and human health may offset this extra cost in circumstances where the use of polymeric flocculants is undesirable or prohibited (Lee et al 2014). In addition, the sludge or flocs formed are biodegradable and safely to be landfilled without further treatment and would reduce the overall treatment cost.…”
Section: Comparison Of Sludge Dewatering Abilities Of Bio-flocculantsmentioning
confidence: 99%
“…Industries such as food, mineral, chemical, pharmaceutical and cosmetic, in addition to the latest production technologies, are trying to improve waste treatment and wastewater treatment technologies [14] . Application of eco-friendly plant-based bioflocculants in wastewater treatment has attracted significant attention lately with high removal capability in terms of solids, turbidity, color, and dye.…”
Section: Introductionmentioning
confidence: 99%
“…Flocculating methods have an immediate effect on the suspended particle size, that is, a larger size results in more rapid settling down of particles. 17 Zhang et al (2014) 18 reported that the selection of the occulant type presents a signicant effect on the capacity of the occulating techniques, potency of the accumulated particles, and the degree of bond stability as a consequence of the occulation process. However, regardless of the signicant effectiveness of the occulating practices in water treatment, the main disadvantage of occulation is the production of breakable ocs at low temperatures; these ocs can scatter the applied physical force.…”
Section: Introductionmentioning
confidence: 99%
“…1 Therefore, "green technology" bioocculants have attracted increasing methodical and technical consideration in environmental wastewater treatment because they are non-hazardous to humans, possess biodegradable constituents, and become free from pollutants by intermediate deprivation. 19 In addition, bioocculants have been generally involved in different applications, such as cleaning up of wastewater, decontamination of organic substance components from sugar, dewatering, dredging, pulp and paper industry, and condensation of mine wastes. 14,20 A high cost prevents the advancement of bio-occulants for marketable use.…”
Section: Introductionmentioning
confidence: 99%